PENGARUH PRICE EARNING RATIO, PROFITABILITAS, DAN KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN (Study Kasus Pada Perusahaan Sub Sektor Plastik dan Kemasan Yang Terdaftar di BEI Periode 2015-2017) - Lujeng Indra Prayugi; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
Abstract This study aims to analyze the effect of price earnings ratio, profitability, and funding decisions on firm value. The purpose of this study is (1) To determine the effect of price earning ratio on firm value (2) To determine the effect of profitability on firm value (3) To determine the effect of funding decisions on firm value. This type of research is explanatory research, this study takes samples from the population using purposive sampling techniques. Case study of plastic and packaging sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The results of this study are (1) Price earning ratio has positive and insignificant effect on firm value (2) Profitability has a negative and significant effect on firm value (3) Funding decisions have a positive and not significant effect on firm value. Keywords: Price Earning Ratio, Profitability, Funding Decision, Company Value, Capital Structure